The Existence of Women in Harian Neraca Press 1989-1994 - *Ratih Tri Kuswati; Tri Yuniyanto; Dadan Adi Kurniawan (Universitas Syiah Kuala, 2022)
The purpose of this study was to find out how the existence of women in the social, economic, political fields in the Harian Neraca newspaper in 1989-1994. The method used in this research is historical. This research was conducted using the archives of the Harian Neraca newspaper in 1989-1994, and literature, both in the form of books and reports of previous research results. The data collection techniques using document study techniques and literature studies. The data analysis technique was carried out by descriptive content analysis. The approach used is a multidimensional approach covering sociology, economics and political science. Based on the results of the study, it can be concluded that the existence of women in the social field in the Harian Neraca newspaper in 1989-1994, among others, highlighted the participation of women in various social activities around the world of public health, community welfare, environmental preservation, education, and cultural preservation. The existence of women in the Harian Neraca newspaper in 1989-1994 in the economic field, among others, discussed the news about the activities of women in industry and women's organizations based on the economy (IWAPI) and the role of women in economic activities on a national scale. The existence of women in the Harian Neraca newspaper in 1989-1994 in the political field, among others, highlighted the problems dominated by Kowani's involvement in fighting for women's rights.